NEW YORK STATE TAX INCREASE - TODD,D (Tufts Archival Research Center, 2007)
Memo regarding the cigarette tax increase in New York State. Summarizes the background of the tax and then shows the trend in sales in New York and the surrounding states after the ban. Compares the sales records in New York of different brands. Shows an increase in discount brands in the state.